THE USE OF PRE-QUESTIONING IN IMPROVING STUDENTS’ READING COMPREHENSION - Mustika, Yeni; Dashela, Tarina (Jurnal Ilmiah Spectral, 2022)
The goal of this research is to describe the students’ improvement in reading comprehension by using pre-questioning. This research was a classroom action research with two cycles conductedto the seventh-grade students of MTS Darussalam Sengkubang. The 7B class was the subject of this research consisting of 29 students. Planning, acting, observing, and reflecting consisted in each cycle. Field notes, observation checklists, interview, and individual test were used as the tools to collect the data. The finding of this research showed that by conducting teaching and learning reading by pre-questioning as a brainstorming activity before read the text could stimulate and allowed the students predict by kept trying to answer the pre-questions given by the teacher. Students tried to found the information asked to them. Thus, the pre-questioning activity made the teaching and learning process of reading was interactive. It also affected the students’ motivation in reading learning process. It was effective and very helpful for the teacher in teaching reading comprehension.